Apoptosis inhibitor of macrophage differentiates bacteria from influenza or COVID-19 in hospitalized adults with community-acquired pneumonia. Issue 4 (April 2022) - Lai, Xiaofei; Wang, Jing; Duan, Jun; Gong, Yi; Cao, Ju
Highlights: AIM levels were higher in bacterial pneumonia compared to influenza pneumonia. AIM levels were higher in bacterial pneumonia compared to COVID-19 pneumonia. AIM might be a biomarker in distinguishing between bacterial and viral pneumonia.